SISTEM PAKAR MENDIAGNOSA PENYAKIT PERUT DENGAN METODE CERTAINTY FACTOR BERBASIS WEB - Nency Extise Putri; Rifa Turaina; Irvan Irvan (Ensiklopedia of Journal, 2021)
Stomacth disease is a disease that can be suffered by all people from children to adults. This diseases cause due to luck of healthy lyfestyle, such as over consuming fast food, unhygienic food or something unhealthy food, then lack of exercise also causes the stomach pain. One of the common methods in diagnosing stomach pain still have to visit and make consultation with the doctor. It tokes time to conduct face to face consultation and pay expensive cost for it. Many stomach disease sufferers do not know the type of stomach disease they experience because of the lack of information about stomach ailments, symptoms and the lack of abdominal specialist doctors. The method used is the method of Certainty Factor (CF) or the certainty value of an illness. Therefore, the purpose of this study is to make expert system software that is expected to help the community or patients in diagnosing the type of Stomacth disease. The development of expert system software includes, software requirements analysis which consists of user needs analysis, analysis of admin requirements. The results of the study were expert system application programs that were able to diagnose 24 stomach diseases. Keywords: Expert system, Certainty Factor, Diagnoses, Stomacth Diases.